2009
DOI: 10.1016/j.pec.2008.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the “nature” and “specific effectiveness” of clinical empathy: A theoretical overview and contribution towards a theory-based research agenda

Abstract: Due to the complexity and multidimensionality of CE, evidence-based investigations of the derived hypotheses require both well-designed qualitative and quantitative studies as well as an interdisciplinary research approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
252
2
28

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 313 publications
(289 citation statements)
references
References 82 publications
7
252
2
28
Order By: Relevance
“…São ainda demostrativos de que os pais desejam ter um papel ativo de colaboração e parceria com o profissional de saúde (Choi, et al, 2010) que quando se efetiva, conduz a uma menor procura de consultas de emergência, a melhoria nos indicadores saúde, e a maior satisfação pais (Knapp, et al, 2011;Weiss, et al, 2010). Por sua vez o fator "Relacional/Emocional" é consonante com a importância atribuída às atitudes positivas dos profissionais como determinante da adaptação dos pais e da própria relação estabelecida com a equipa de saúde (Barnard, et al, 1990;Kenney, et al, 2011;Knapp, et al, 2011) na qual a empatia é particularmente valorizada pelos pais (Neumann, et al, 2009;Ordem dos Enfermeiros, 2010).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…São ainda demostrativos de que os pais desejam ter um papel ativo de colaboração e parceria com o profissional de saúde (Choi, et al, 2010) que quando se efetiva, conduz a uma menor procura de consultas de emergência, a melhoria nos indicadores saúde, e a maior satisfação pais (Knapp, et al, 2011;Weiss, et al, 2010). Por sua vez o fator "Relacional/Emocional" é consonante com a importância atribuída às atitudes positivas dos profissionais como determinante da adaptação dos pais e da própria relação estabelecida com a equipa de saúde (Barnard, et al, 1990;Kenney, et al, 2011;Knapp, et al, 2011) na qual a empatia é particularmente valorizada pelos pais (Neumann, et al, 2009;Ordem dos Enfermeiros, 2010).…”
Section: Discussionunclassified
“…A empatia é definida como "a perceção do quadro de referências do outro incluindo os componentes emocionais e de significados, como se do próprio se trata-se, sem que no entanto se perca o "se" como condição" (Rogers, 1959, p. 201-211). Deste modo, a empatia envolve atitudes de descentração do referencial do próprio, de neutralidade e sobretudo abertura à compreensão das reações e necessidades parentais considerando as suas crenças e o seu contexto (Neumann, Bensing, Mercer, Ernstmann, & Pfaff, 2009).…”
unclassified
“…It may indicate that emotional self-efficacy is a measurement of the cognitive components of empathy, but emotional intelligence refers to the emotional constituents of empathy. In a review of studies on empathy in the medical practice, Neumann et al (2009) found that personal distress and sympathy correlated with an affective reaction, but perspective taking was associated with self-efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, empathy is an accurate understanding of the experience of the sufferer leading to an attuned response from the observer. 3 Clinical empathy is an essential element of quality care, and is associated with improved patient satisfaction and adherence to treatment, as well as fewer malpractice complaints. 4 Indeed, many of the criticisms of medical care voiced by patients refer to what they perceive as inadequate interpersonal and communication skills rather than deficiencies in the technical or procedural aspects of their care.…”
Section: What Is Empathy?mentioning
confidence: 99%